Carbon nanofiber—sodium alginate composite aerogels loaded with vitamin D: The cytotoxic and apoptotic effects on colon cancer cells - BİNGÖL ÖZAKPINAR, ÖZLEM (My University, 2023)
Colorectal cancer (CRC) is the fourth most commonly diagnosed cancer and the third leading cause of cancer-related deaths worldwide. A substantial body of literature supports the crucial role of vitamin D (VD) in the etiology, progression, prognosis, and treatment of cancer. Recent clinical studies have found an inverse correlation between CRC incidence and serum VD levels. However, the low water solubility of VD and its anticarcinogenic activity at supraphysiological plasma levels, which causes hypercalcemia, required carrier systems. Carbon-based nanomaterials are excellent eco-friendly candidates, with exceptional chemical resistance, efficient mechanical properties, and negligible weight. Furthermore, composite aerogels manufactured from these nanomaterials have gained interest due to their extensive surface areas and porous structures, which make them suitable for delivering drugs. Our research aimed to study the development of composite aerogels loaded with VD by utilizing carbon nanofibers (CNFs) in an aerogel matrix provided to colon cancer cells. For this purpose, Aero1 as a drug delivery system was first prepared and characterized using XRD, FTIR, and SEM methods. Biochemical methods were employed to evaluate the antiproliferative, apoptotic, and anti-migratory effects on colon cancer cells. FTIR and XRD measurements confirmed the production of aerogels. SEM analysis revealed that aerogels have a non-uniform surface. The findings showed that aerogels can effectively deliver VD to the colon cancer cells, while also inhibiting cancer cell proliferation and migration. This research suggests that the Aero1 drug delivery system could be a valuable tool in the fight against colon cancer and other health issues.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Biyokimya; Sağlık Bilimleri; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Biochemistry; Health Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; Clinical Medicine (MED); Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; PHARMACOLOGY & PHARMACY; Farmakoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); İlaç Rehberleri; Yaşam Bilimleri; Pharmacy; Pharmacology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); Drug Guides; Life Sciences; vitamin D; drug delivery system; carbon nanofiber; aerogel; colon cancer cells; apoptosis